Stearoyl-CoA desaturase (scd1a) is epigenetically regulated by broodstock nutrition in gilthead sea bream (Sparus aurata). Issue 5 (3rd May 2020) - Perera, Erick; Turkmen, Serhat; Simó-Mirabet, Paula; Zamorano, Maria J.; Xu, Hanlin; Naya-Català, Fernando; Izquierdo, Marisol; Pérez-Sánchez, Jaume
ABSTRACT: The aim of this study was to generate new knowledge on fish epigenetics, assessing the effects of linolenic acid (ALA) conditioning of broodstock in the offspring of the marine fish Sparus aurata . Attention was focused on gene organization, methylation signatures and gene expression patterns of fatty acid desaturase 2 ( fads2 ) and stearoyl-CoA desaturase 1a ( scd1a ). Blat searches in the genomic IATS-CSIC database (www.nutrigroup-iats.org/seabreamdb ) highlighted a conserved exon-intron organization, a conserved PUFA response region, and CG islands at the promoter regions of each gene. The analysed CpG positions in the fads2 promoter were mostly hypomethylated and refractory to broodstock nutrition. The same response was achieved after conditioning of juvenile fish to low water oxygen concentrations, thus methylation susceptibility at individual CpG sites seems to be stringently regulated in fish of different origin and growth trajectories. Conversely, the scd1a promoter was responsive to broodstock nutrition and the offspring of parents fed the ALA-rich diet shared an increased DNA-methylation, mainly in CpG sites neighbouring SP1 and HNF4α binding sites. Cytosine methylation at these sites correlated inversely with the hepatic scd1a expression of the offspring. Co-expression analyses supported that the HNF4α-dependent regulation of scd1a is affected by DNA methylation. The phenotypic output is a regulated liver fat deposition through changes in scd1 expression, which would also allow the preservation of fatty acid unsaturation levels in fish fed reduced levels of n-3 LC-PUFA. Collectively, these findings reveal a reliable mechanism by which parent's nutrition can shape scd1a gene expression in the fish offspring.